2022
DOI: 10.1002/jhet.4457
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of chiral diamides as organocatalysts in asymmetric aldol reaction

Abstract: Seven novel proline and 1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid (THIQA) based diamides were synthesized successfully by simple amidation reactions and characterized by their spectral data. Their catalytic activities in asymmetric aldol reaction were performed by the reactions of aliphatic ketones and various aromatic aldehydes. Especially, (S)-N-((S)-1-(morpholinoamino)-1-oxo-3-phenylpropan-2-yl)pyrrolidine-2-carboxamide (9e) showed good catalytic activities in water at room temperature in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In 2021-2022, Yolacan and colleagues reported that chiral Pro-Phe-derived dipeptide catalysts with an aromatic acid as the co-catalyst exhibited higher catalytic activity in water than in other solvents when catalyzing the asymmetric aldol reactions of aliphatic ketones with aromatic aldehydes (Scheme 2a). 8,9 In 2021, Makatini and coworkers reported a solid-phase peptide-promoted aldol reaction between ketones and aldehydes (Scheme 2b). 10 Addition of a small amount of water was beneficial for yield and stereoselectivity.…”
Section: Water-enabling Improvement Of Reactivity or Stereoselectivitymentioning
confidence: 99%
“…In 2021-2022, Yolacan and colleagues reported that chiral Pro-Phe-derived dipeptide catalysts with an aromatic acid as the co-catalyst exhibited higher catalytic activity in water than in other solvents when catalyzing the asymmetric aldol reactions of aliphatic ketones with aromatic aldehydes (Scheme 2a). 8,9 In 2021, Makatini and coworkers reported a solid-phase peptide-promoted aldol reaction between ketones and aldehydes (Scheme 2b). 10 Addition of a small amount of water was beneficial for yield and stereoselectivity.…”
Section: Water-enabling Improvement Of Reactivity or Stereoselectivitymentioning
confidence: 99%